2017
DOI: 10.1074/jbc.m117.775999
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the type II transmembrane serine protease, TMPRSS13, in hepatocyte growth factor activator inhibitor-1 and -2–mediated cell-surface localization

Abstract: TMPRSS13 is a member of the type II transmembrane serine protease (TTSP) family. Although various TTSPs have been characterized in detail biochemically and functionally, the basic properties of TMPRSS13 remain unclear. Here, we investigate the activation, inhibition, post-translational modification, and localization of TMPRSS13. We show that TMPRSS13 is a glycosylated, active protease and that its own proteolytic activity mediates zymogen cleavage. Full-length, active TMPRSS13 exhibits impaired cell-surface ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 43 publications
(74 reference statements)
7
48
0
Order By: Relevance
“…Western blot results showed that target bands were examined but the immunoreactive bands are not unique, which is consistent with previous work [26]. We speculated that serine proteases TMPRSS2 and MSPL, the glycosylated proteins, showed multiple cut bands with different sizes by their own proteolytic activity [58]. Moreover, the results indicated that the bands, larger than the target bands (TMPRSS2,82 kDa; MSPL, 89 kDa), were detected in this study, and we speculated that caused by phosphorylation [58].…”
Section: Discussionsupporting
confidence: 90%
“…Western blot results showed that target bands were examined but the immunoreactive bands are not unique, which is consistent with previous work [26]. We speculated that serine proteases TMPRSS2 and MSPL, the glycosylated proteins, showed multiple cut bands with different sizes by their own proteolytic activity [58]. Moreover, the results indicated that the bands, larger than the target bands (TMPRSS2,82 kDa; MSPL, 89 kDa), were detected in this study, and we speculated that caused by phosphorylation [58].…”
Section: Discussionsupporting
confidence: 90%
“…Next, to explore the functional aspects of the molecular interaction between DC-SIGN and MSPL/TMPRSS13, we constructed a plasmid containing the MSPL extracellular domain (MSPL-ECD). A stable transfectant of MSPL-ECD showed multiple bands after CBB staining (Figure 3a), as previously reported [24], due to self-cleavage and glycosylation variants. When we conducted the DC-SIGN-ECD lectin blot assay, we found that DC-SIGN-ECD binds to MSPL-ECD in a Ca 2+ -dependent manner (Figure 3b) and that all self-digested peptide fragments contained DC-SIGN-bindable glycans.…”
Section: Glycan-dependent Recognition Of Mspl By Dc-signsupporting
confidence: 86%
“…It has been reported that MSPL/TMPRSS13 retains its protease activity when it is phosphorylated, shed, and released from the cell surface [24]. Next, to explore the functional aspects of the molecular interaction between DC-SIGN and MSPL/TMPRSS13, we constructed a plasmid containing the MSPL extracellular domain (MSPL-ECD).…”
Section: Glycan-dependent Recognition Of Mspl By Dc-signmentioning
confidence: 99%
See 1 more Smart Citation
“…The refined model contains the hMSPL with the residue range of 188-558, except 319 and 320, decanoyl-RVKR-cmk, and a calcium ion. Glycans attached to residues Asn250 and Asn400 were observed, but no phosphorylated residues found (18).…”
Section: Overall Structure Of the Mspl Extracellular Domainmentioning
confidence: 94%